Junior high school students’ difficulties of English language learning in the speaking and listening section - Jaelani, Alan; Zabidi, Olivia Widad (ELT Forum: Journal of English Language Teaching, 2020)
This study aims to determine students' problems in learning English, especially in terms of speaking and listening. Basically, the teaching and learning process will run smoothly if students feel comfortable with the learning activities; therefore, this research provides some appropriate suggestions for teachers in overcoming difficulties faced by students. The respondents of this study were junior high school students. This study used a questionnaire as an instrument to determine the extent of students' skills in English. This study also conducted data analysis by analyzing the importance of English in students' views, the difficulties encountered in learning English, and also the teacher's teaching strategies desired by students. The results of this study indicate that most students have some difficulties in speaking due to lack of confidence and skills such as pronunciation, vocabulary, and grammar. Likewise, the difficulty in listening is caused by students’ lack of vocabulary that leads to the difficulty in understanding conversations in English. To overcome this problem, teachers need to have strategies such as identification, diagnosis, prognosis, and assistance or therapy. This research can facilitate the teachers in knowing complaints about English language difficulties experienced by the students.